Mengurangi Perilaku Agresivitas Verbal Melalui Teknik Token Ekonomi Pada Siswa Kelas III-A UPT SD Negeri 23 Gresik - Fitri, Ananda (Jurnal Psikologi Terapan, 2024)
One of the deviant behaviors commonly found in schools is aggressive behavior. One form of aggressiveness is verbal. One effort that can be made to overcome verbal aggressive behavior is to modify this behavior. One behavior modification technique is token economics. The method used in this research is the Single Subject Research (SSR) method using an A-B-A design which is divided into three phases, namely: baseline-1, intervention and baseline-2 phases. Based on the results of the program that has been carried out, it can be concluded that the verbal aggressive behavior of class III-A students at UPT SD Negeri 23 Gresik can be reduced using the economic token technique.